Mitigasi Risiko Produksi Sirup Pala pada UKM Mysari Pala - Rosandi, Adelia; Anjani, Silfi Rafa; Putri, Elvina Farica Cipto; Subagja, Rahmat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
The risk in processing nutmeg syrup occurs in the My Sari Pala UKM. The presence of nutmeg that does not meet standards or is defective is a risk for Mysari Pala and can cause prolonged losses in the product production process. This research was conducted to determine the incidence of risks, impacts and risk mitigation in the My Sari Pala UKM. Risk calculations are carried out using the House of Risk (HoR) method. HoR is divided into 2 phases, where phase 1 is the phase of identifying events and risk agents, while phase 2 is the phase of designing mitigation strategies to effectively handle risk agents that will be implemented in UKM Mysari Pala. Found 14 risk events, 14 risk agents, 8 risk agents that were priorities and 6 others that were non-priorities. There are 14 handling strategies from risk agents with the 3 highest handling strategies based on ETD, namely making SOPs regarding specifications for nutmeg suitable for processing (PA6), placement of suppliers (PA2), regular temperature monitoring (PA11).